LIRAGLUTIDE PLEIOTROPIC EFFECT IN CARDIOVASCULAR RISK REDUCTION IN TYPE 2 DIAbETES — A MANDATE FOR CARDIOLOGIST AND INTERNIST - S. V. Nedogoda (Российский кардиологический журнал, 2018)
The data from a range of large trials (LEADER, EMPA-REG, CANVAS) show evidently the practical use of the modern glucose lowering drugs usage for successful management of cardiovascular risk in type 2 diabetes (DM2) patients. The article is focused on analysis and review of possible mechanisms and benefits of cardiovascular risk reduction in DM2 with prescription of the antagonist of glucagonlike peptide 1 — liraglutide (Victoza®).